The effect of an educational program on kinetic interdependence to develop the technical and digital performance of the long jump event for beginners (Journal of the College of Basic Education, 2023)
The research consist of five chapters, the first chapters contain the introduction and how importance it is , a review been taken on the education filed and programmed Instruction and how the learning process aims at preparing and developing the level of athlete who is prone to learning programs put according to scientific method , the development comes as result to used the basic principles of motor learning , and selection and design learning programming for the scientific basic and used to achieve education aims in long jump specially . the more importance point in this research in using a relation between the movement with each other (Association) subject programmed instruction for the learning indicators and jump results , the problem of this study lurks in the little interest which teacher pay to the modern programmed Instruction at some times it happened randomly ,that's why the researcher put the aims of the study and the purposes according to the research title as its been specified the human mechanic and timing levels. the second chapter contain the motor learning and programmed Instruction , a relation between the movement with each other (Association) subject ,the artistic performance of long jump skill .the third chapter contain the educational details in the research the researcher used the experimental subject to achieve the one of field procedure search , the fourth chapter contain showing the results in tables shapes and mathematic ways according to the procedures statistics . the fifth chapter one contain the recommendations final results.